ANALISIS PENGARUH FAKTOR EKSTERNAL DAN INTERNAL PERBANKAN TERHADAP LIKUIDITAS PERBANKAN SYARIAH DI INDONESIAPERIODE JANUARI 2003 OKTOBER 2015 - Lina Nugraha Rani (al-Uqud : Journal of Islamic Economics, 2017)
Liquidity is the fulfillment of bank liabilities that must be considered in the Islamic banking operations and errors in the management of liquidity can cause loss of Islamic banking which have an impact on the decline for the profit sharing to deposits customers and shareholders of Islamic banking. This study was to investigate the influence of external factors (Economic Performance (EK), inflation (INF), the Global Financial Crisis (D07)) and internal (Non Performing Financing (NPF) and Rate of Return (Deposit)of banks to liquidity (FDR) of Sharia Banking in Indonesia.Data were collected on a monthly basis from January 2003 - October 2015 times series data are tested by unit root and cointegration using Eviews 6.1. to determine the relationship between the variables in the long run.Based on the results of cointegration tests indicate that in long term relationships, NPF and EK variables have a significant and negative influence on the FDR, RRD variables have significant and positive influence on the FDR while variable INF and D07 does not have a significant influence on the FDR. It can be concluded that the Islamic banking must pay attention to the increase in marketing of Islamic banking products to increase liquidity despite good economic conditions and lower financing problems to increase the liquidity of Islamic banking.